Gas exchange and photosynthetic pigments in bell pepper irrigated with saline water - Hidelblandi F. de Melo; Edivan R. de Souza; Heitor H. F. Duarte; Jailson C. Cunha; Hugo R. B. Santos (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The tools that evaluate the salinity effects on plants have great relevance as they contribute to understanding of the mechanisms of tolerance. This study aimed to evaluate gas exchanges and the contents of photosynthetic pigments in bell peppers cultivated with saline solutions (0, 1, 3, 5, 7 and 9 dS m-1) prepared using two sources: NaCl and a mixture of Ca, Mg, K, Na and Cl salts, in randomized blocks with a 6 x 2 factorial scheme and 4 replicates, totaling 48 experimental plots. The net photosynthesis (A), stomatal conductance (gs), transpiration (E), internal CO2 concentration (Ci), instantaneous carboxylation efficiency (A/Ci) and water use efficiency (WUE), besides chlorophyll a, b and carotenoids were evaluated. The gas exchange parameters were efficient to indicate the effects of salinity. All photosynthetic pigments decreased with increased electrical conductivity, and the chlorophyll a is the most sensitive to salinity, while the water use efficiency increased with the increment of electrical conductivity.